An Ethereum-based wind power energy network contract management solution. (3rd January 2022) - Zhang, Lihua; Bai, Jiayi
Because the existing wind turbine safety is limited by the traditional centralised management, it faces many security risks. Therefore, the future wind turbine management and control scheme is developing towards distributed security and high performance. Relying on Ethereum block technology to build smart contracts can help solve the security protection problems of network authority control and management in wind power energy systems. First, based on the analysis of wind power network security management needs, establish a mathematical model of security indicators for the control centre and subordinate nodes, respectively, when the permissions are out of control; second, based on the Ethereum smart contract release platform, according to the mathematical model of security indicators run wind power contract management (WPCM), predict the results of out-of-control simulation, and compare with the communication parameters of a typical wind farm in Northwest Europe. Studies have shown that the established wind power energy network security management plan has the characteristics of high security and good robustness, and the system processing speed is fast, which meets the offshore wind farm communication standard.